Verbal instructions acutely affect drop vertical jump biomechanics - Implications for athletic performance and injury risk assessments - Khuu, S.; Musalem, L. L.; Beach, T. A. C. (The Journal of Strength and Conditioning Research, 2015)
Biomechanical quantities acquired during the drop vertical jump (DVJ) are used in the assessment of athletic performance and injury risk. The objective was to examine the impact of different verbal instructions on spatiotemporal, kinematic, and kinetic variables commonly included in such assessments. Ten men and 10 women from local varsity and club volleyball, basketball, figure skating, and track and field teams volunteered to participate. The athletes performed DVJs after given instructions to minimize ground contact time (CT), maximize jump height (HT), and synchronously extend the lower extremity joints (EX). Between the CT, HT, and EX conditions, body segment and joint angles were compared together with characteristics of vertical ground reaction force (GRF), whole-body power output, stiffness, and center-of-mass displacement time histories. Verbal instructions were found to influence nearly all of the spatiotemporal, body segment and joint kinematic, and kinetic variables that were statistically analyzed. Particularly noteworthy was the finding that athletic performance indices (e.g., jump height, power output, vertical stiffness, and reactive strength index) and lower extremity injury risk markers (e.g., peak vertical GRF and frontal plane knee angle) were significantly different (p = 0.05) between the CT, HT, and EX conditions. The findings of this study suggest that verbal instructions should be controlled and/or clearly documented when using the DVJ to assess athletic performance potential and injury risk. Moreover, practitioners who devise performance enhancement and injury prevention strategies based on DVJ assessments are advised to consider that "coaching" or "cueing" during the task execution could impact conclusions drawn.